Efektivitas Undang-Undang Tindak Pidana Korupsi Sebagai Alat Rekayasa Sosial - Weenas, Andi Harunsyah Peter Noel (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2024)
The rampant corrupt behaviour that occurs in Indonesia is an unfortunate irony to the integrity of the state and legal apparatus. The Corruption Act is supposed to be a guideline for a clean society that is free from fraudulent and corrupt behaviour. Ironically, the current reality proves that the existence of the Corruption Act is not strong enough to eradicate the chain of corruption. Corruption not only undermines state stability but also hinders national development. Furthermore, it is a violation of human rights and the fundamental values that underpin a nation. This article discusses the role of the Corruption Act as a tool of social engineering throughout society, with particular focus on its status as a written rule and in the context of law enforcement of the Act. Furthermore, the purpose of this research is to examine further the application of the Corruption Act from the aspect of substance in the community. Therefore, this research uses a normative juridical approach. Considering that the eradication of corruption is not something as simple as turning the palm of the hand, in the application of the law it is important to implement good collaboration between institutions and the society. Suggestions must be made to strengthen and tighten supervision in law enforcement, and social education for the community on the importance of having awareness of how destructive and destructive corrupt behaviour is.